Desarrollo De Un Sistema Experto Para Mejorar La Asignacion Del Docente A Las Diferentes Catedras En La Facultad De Informática Y Electrónica Utilizando El Modelo De Mycin - Jonny Israel Guaiña Yungán; Byron Ernesto Vaca Barahona; Carlos Arturo Jara Santillán; Ángel Patricio Flores Orozco; Sttefano Israel Aguayo Cáceres (European Scientific Journal, ESJ, 2017)
This research proposes the development of an expert system that improves the teaching assignment to teach the different chairs of the Faculty of Computer Science and Electronics at the Polytechnic School of Chimborazo. The current problem involves a manual process of evaluation of academic profiles and find the best solution through an expert system that meets certain needs when assigning chairs to the teacher. Free software was used. Linux Platform CentOS 5.0, Glassfish Server 3.1.2, PostgreSQL Database Version 9.2, Java Programming language with PrimeFaces 4.0 component library to automate, optimize and properly focus the assignment process. Based on a Likert scale, the automated process was 93.33% efficient versus 33.33% of the manual process. Analyzing the results, it is concluded that the automatic process exceeds the manual process by 60%, revealing that the process of assigning chairs has improved considerably using this expert system. The use of this system will support and guide decisions when evaluating academic profiles of professionals who would like to be part of the faculty of the Faculty of Computer Science and Electronics at the Polytechnic Higher School of Chimborazo.